2016
DOI: 10.1186/s40064-016-3680-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence among toxic and non-toxic cyanobacteria of the dry zone of Sri Lanka

Abstract: Sri Lanka has rich cyanobacterial diversity, however, only few studies have been conducted to identify the potential toxin producers in water bodies used for human consumption. As the detection of cyanotoxin is vital in water quality management, a study was done by employing 16S rRNA gene to explore the genetic divergence, phylogenetic relationships and potential toxin producing cyanobacteria in reservoirs and well waters in the dry zone of Sri Lanka. Forty five, 16S rRNA gene sequences were assayed and phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
(63 reference statements)
1
5
1
1
Order By: Relevance
“…was reported in 17 reservoirs of fresh water bodies in Sri Lanka by Jayatissa et al [7]. Genetic divergence, phylogenetic relationships and potential toxin producing cyanobacteria in reservoirs and well waters in Dry zone of Sri Lanka have been studied using 16S rRNA gene sequences by Liyanage et al [8]. This study confirms a rich diversity and divergence among toxin producing cyanobacteria in the water bodies in Dry zone in Sri Lanka [8].…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…was reported in 17 reservoirs of fresh water bodies in Sri Lanka by Jayatissa et al [7]. Genetic divergence, phylogenetic relationships and potential toxin producing cyanobacteria in reservoirs and well waters in Dry zone of Sri Lanka have been studied using 16S rRNA gene sequences by Liyanage et al [8]. This study confirms a rich diversity and divergence among toxin producing cyanobacteria in the water bodies in Dry zone in Sri Lanka [8].…”
Section: Introductionsupporting
confidence: 65%
“…Of these, except for Microcystis aeruginosa, other species are either rare or occur only in small numbers [37]. More recent reports on the occurrence of freshwater cyanobacteria give evidence of Cylindrospermopsis as a dominant form in addition to Microcystis in several reservoirs surveyed [5,8,38]. However in the present study Cylindrospermopsis was not observed among the genera isolated and cultured.…”
Section: Intermediate Zonecontrasting
confidence: 56%
See 1 more Smart Citation
“…Sri Lanka is a tropical island enriched with remarkable floral, faunal, and microbial diversity. Diverse ecosystems representing a range of environmental conditions facilitate unlimited ecosystems for cyanobacterial distribution in Sri Lanka, contributing to a higher diversity (Kulasooriya and de Silva, 1981;Kulasooriya and Magana-Arachchi, 2016;Liyanage et al, 2016;Hossain et al, 2017;Hossain et al, 2020a). The occurence of cyanobacteria has been reported in reservoiurs of Sri Lanka (Silva and Wijeyaratne, 1999;Hossain et al, 2017;Senanayake and Yatigammana, 2017).…”
Section: Research Articlementioning
confidence: 99%
“…A sample that has undergone the complete treatment at this plant was negative for CYN showing that the treatment has been effective in eliminating the toxin. These determinations were confirmed and quantified by the application of High Performance Liquid Chromatography (HPLC) using CYN standards (Liyangae et al, 2014) Subsequently Liyanage et al (2016c) published detail results of toxins identified from cyanobacteria isolated and cultured in the laboratory as well as from unculturable taxa using molecular techniques primarily based upon the 16srRNA genes. This study has been done on water samples collected from Tisawewa, Nuwarawewa, Kalawewa, Jayaganga and Nacchchaduwawewa in the Anuradhapura district, Ulhitiyaand MinipeEla reservoirs in Girandurukotte in the Polonnaruwa district and Nikawewa in the Kurunegala district, all major CKDu prevalent areas in the dry zone.…”
Section: Cyanobacterial Toxinsmentioning
confidence: 99%